Trends in the effects of socioeconomic position on physical activity levels and sedentary behavior among Korean adolescents - Hunju Lee; Hyowon Choi; Sang Baek Koh; Hyeon Chang Kim (Epidemiology and Health, 2023)
OBJECTIVES We examined trends in physical activity and sedentary behavior in Korean adolescents, and their association with socioeconomic position (SEP). METHODS We used data from the Korea Youth Risk Behavior Survey, a nationwide study involving students aged 12-19 conducted between 2009 and 2021. SEP was assessed based on economic status, parental education attainment, and urbanization. Physical activity was categorized into vigorous physical activity, moderate physical activity, and muscle training, and sedentary time was also measured. We conducted the log-binomial regression to calculate prevalence ratios (PRs) and prevalence differences. RESULTS Our analysis included a total of 593,896 students. We observed an increasing trend in physical activity, but a worsening trend in sedentary behavior. A positive association was found between an adolescent’s physical activity and SEP indicators, except for urbanization. Adolescents with higher economic status engaged in more vigorous physical activity (high: PR, 1.26; 95% confidence interval [CI], 1.25 to 1.28; middle: PR, 1.03; 95% CI, 1.02 to 1.04). Similar associations were observed for father’s education (tertiary or above: PR, 1.11; 95% CI, 1.09 to 1.13; upper secondary: PR, 1.05; 95% CI, 1.03 to 1.07) and mother’s education (tertiary or above: PR, 1.17; 95% CI, 1.15 to 1.20; upper secondary: PR, 1.06; 95% CI, 1.04 to 1.08). Adolescents with higher economic status also showed a higher compliance rate with the guideline restricting sedentary time to 2 hours per day (high: PR, 1.28; 95% CI, 1.25 to 1.30; middle: PR, 1.03; 95% CI, 1.01 to 1.05). CONCLUSIONS Adolescents with higher SEP exhibited more physical activity and less sedentary time than those with lower SEP.